1. The problem statement, all variables and given/known data Show [itex]f(x) = x^3-x^2+x-1[/itex] is never decreasing. 2. The attempt at a solution [itex]f(x) = x^3-x^2+x-1[/itex] [itex]f'(x) = 3x^2 - 2x + 1[/itex] [itex]f''(x) = 6x - 2[/itex] 3. The problem that I'm facing I don't understand what it means by never decreasing. Do I say that when differentiates, it gives a positive quadratic equation hence it never decreasing or when differentiated twice, it forms a positive linear equation hence never decreasing?